2021
DOI: 10.1002/dc.24743
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of accuracy of fine‐needle aspiration biopsy for breast lesions using the International Academy of Cytology Yokohama System for reporting breast cytopathology

Abstract: Background Classification of breast lesions into different cytological groups can accurately be done using the International Academy of Cytology (IAC) Yokohama System for reporting breast cytopathology. Fine needle aspiration biopsy (FNAB) of breast lesions has been considered to be the primary investigation in detecting breast cancers, especially in low‐cost settings. The main objective of this study was to prospectively re‐confirm the diagnostic accuracy of breast FNAB using the IAC Yokohama system. Addition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…All 18 eligible studies were published between 2019 and 2021, and most of them (n = 11) were conducted in India. Most were retrospective (n = 16), whereas two 19 , 30 followed a prospective design. None of the authors reported the sole use of liquid-based cytology as their cytopreparation method.…”
Section: Resultsmentioning
confidence: 99%
“…All 18 eligible studies were published between 2019 and 2021, and most of them (n = 11) were conducted in India. Most were retrospective (n = 16), whereas two 19 , 30 followed a prospective design. None of the authors reported the sole use of liquid-based cytology as their cytopreparation method.…”
Section: Resultsmentioning
confidence: 99%
“…These studies report ROM in the different categories of IACYS. The ROM was ranged in categories II 0.4% to 8.3%, III 1.3% to 50%, IV 55.55% to 100%, and V 97% to 100% 4–18 . The ROM in category I without ROSE ranges from 0% to 60.87% 4–18 and 0% to 11.11% 8,17 with ROSE.…”
Section: Discussionmentioning
confidence: 96%
“…В работе S. Agrawal и соавт. (2021) проведена проспективная оценка точности ТИАБ при поражениях молочной железы с использованием Йокогамской системы, в которой авторы показали высокую диагностическую точность для каждой категории BI-RADS [22].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reproductive Systemunclassified